PHYSICOCHEMICAL AND FLUORESCENCE ANALYSIS OF ARTEMISIA NILAGIRICA (CLARKE) PAMP - PARAMESWARI.P,; DEVIKA.R, (International Journal of Pharma and Bio Sciences, 2015)
Artemisia nilagirica of Asteraceae family was commonly known as Sage Brush or wormwood and they were grown for its religious importance due to its immense fragrance. In the present investigation, the various plant parts were segregated separately, washed dried and powdered for future analysis. The various parts of the plant (Root, Stem, Leaves and Flower) were subjected to fluorescence analysis with various chemicals and acid such as Conc. HCl, Conc. H2SO4, Glacial acetic acid, HNO3 5% KOH, Picric acid, Ammonia solution, Petroleum ether, Ethanol, 5% NaOH and FeCl3 and their appearance were observed in day light, UV 254 nm and 365 nm. Further the samples were subjected to physicochemical analysis to evaluate the purity and confirm their therapeutic values.